2007
DOI: 10.1590/s0103-84782007000200003
|View full text |Cite
|
Sign up to set email alerts
|

Toxicidade de agrotóxicos utilizados na cultura do pessegueiro sobre o parasitóide de ovos Trichogramma atopovirilia Oatman & Platner, 1983 (Hymenoptera: Trichogrammatidae)

Abstract: A toxicidade de dezesseis formulações comerciais de agrotóxicos utilizados na cultura do pessegueiro foi avaliada em laboratório (temperatura 25±1oC, umidade relativa 70±10% e fotofase de 14 horas), expondo-se adultos do parasitóide Trichogramma atopovirilia Oatman & Platner, 1983 (Hymenoptera: Trichogrammatidae) em contato com uma película seca dos produtos fitossanitários pulverizados sobre placas de vidro, mensurando-se posteriormente o número de ovos parasitados por fêmea. Reduções na capacidade de par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…The lower toxicity of oxyfluorfen on P. elaeisis agrees with a previous report where this herbicide was found to be only moderately toxic to Trichogramma atopovirilia Oatman and Platner, 1983 (Hymenoptera: Trichogrammatidae) and Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae), with a reduction in parasitism of 95.8% and 95.6%, respectively (Manzoni et al. , 2006; Giolo et al. , 2007).…”
Section: Discussionsupporting
confidence: 90%
“…The lower toxicity of oxyfluorfen on P. elaeisis agrees with a previous report where this herbicide was found to be only moderately toxic to Trichogramma atopovirilia Oatman and Platner, 1983 (Hymenoptera: Trichogrammatidae) and Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae), with a reduction in parasitism of 95.8% and 95.6%, respectively (Manzoni et al. , 2006; Giolo et al. , 2007).…”
Section: Discussionsupporting
confidence: 90%
“…However, divergent results for gamma-cyhalothrin and etofenprox are reported in the literature. Haseeb et al [ 36 ] indicated that gamma-cyhalothrin caused high mortality to adults of the parasitoid Cotesia plutellae (Kurdjumov) (Hymenoptera: Braconidae) when exposed to residues of this insecticide; and Moscardini et al [ 37 ] and Giolo et al [ 38 ] reported high mortality rates of parasitoids when exposed to residues of etofenprox.…”
Section: Discussionmentioning
confidence: 99%
“…Até o momento estão disponíveis informações, para alguns dos principais produtos recomendados nesta cultura, para estágios adultos e imaturos de Trichogramma cacoeciae Marchal, 1927(GRUTZMACHER et al, 2004; estágios adultos e imaturos de Trichogramma pretiosum Riley, 1879(GIOLO et al, 2005 e adultos de T. atopovirilia (GIOLO et al, 2007). Em alguns destes estudos (GRUTZMACHER et al, 2004;GIOLO et al, 2006), ficou demonstrado que, para a grande maioria dos produtos fitossanitários avaliados, seria viável a integração dos métodos de controle químico e biológico e o parasitóide em estágio imaturo de desenvolvimento.…”
Section: Introductionunclassified